AKSELERASI HILIRISASI PRODUK AGROINDUSTRI BERDAYASAING MENDONGKRAK KESEJAHTERAAN PETANI DAN EKONOMI PEDESAAN - Roosganda Elizabeth; Iwan Setiajie Anugrah (Universitas Galuh Ciamis, 2020)
The downstream acceleration of agroindustry products is a shift in the export of raw material products to competitive products that are competitive and meet the high demands of quality and hygienic processed product (GMP) requirements. In the era of globalization and technology 4.0, it is necessary to accelerate the development of agroindustrial products that are competitive and exist in the global market, related to increased income and welfare of farmers, business players of processed products. The importance of changing the mindset by shifting exports of raw products to competitive agroindustry products by developing and improving downstream implementation. With the qualitative description method, it is stated the objective of writing comprehensively about the downstreaming of highly competitive banana agro-industry products enriched by reviewing the results of various studies and related papers. The processing phase starts from the home industry, small and medium business units and exports. Processed products are equipped with data to support analysis, covering the feasibility of: technical, financial, economic, social and environmental, as well as infrastructure and policy support. Several obstacles were identified, such as: limited capital, continuity of the availability of raw materials, bargaining position, marketing and HR of business actors. The development of technological innovation, investment and business human resources through the development of agro-industrial products is predicted to be a